Implikasi Putusan Pengadilan terhadap Keabsahan Perubahan Data Akta Kelahiran dalam Pencatatan Sipil - Marven Ajels Kasenda; Daniel Reihan Palar; Claudio Junior Willem Rambing; Olivia Zefanya Karundeng; Esther Tesalonika Putrigrace Liuw; Sisilia Koloay; Sefania Gloria (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the legal implications of court decisions that have obtained permanent legal force (inkracht) on the validity of changes to birth certificate data. Amendments to civil documents such as birth certificates do not merely involve administrative issues but also directly affect an individual’s legal status. In practice, many people face obstacles when seeking data corrections, especially when discrepancies arise between existing data and supporting documents. This research employs a normative juridical approach by analyzing laws and regulations, legal doctrines, and a case study of the Supreme Court of the Republic of Indonesia Decision No. 587 K/Pdt/2021 as the primary focus. The analysis centers on the legal reasoning adopted by the panel of judges in granting the request for data correction, and how the decision binds the civil registration authority to execute the ordered amendment. The findings reveal that a court decision with permanent legal standing serves as a crucial legal instrument to ensure the validity and legality of population data changes. Moreover, this legal mechanism reinforces civil protection within the national administrative framework. The study also recommends enhancing coordination between judicial institutions and civil registry offices to streamline data correction procedures and prevent legal uncertainty. In this regard, the study provides an academic contribution to the development of administrative law and the protection of citizens' legal rights.